Beyond Satisfaction dalam pemenuhan kepuasan dan loyalitas Konsumen atas layanan jasa Grab di Tulungagung - Maarif, Sultan Hakim; Nurohman, Dede (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The development of the current modern era, one of which is the development of the world of transportation in Indonesia, especially in the city of Tulungagung, is the focus of research, namely the service of Grab drivers, which refers to standard operating procedures from companies for service to consumers in order to fulfill customer satisfaction and loyalty. This study aims to reveal the services provided by Grab drivers in fulfilling customer satisfaction through the implementation of standard operating procedures that apply within the company. This study uses a qualitative method, where the results of the research are in the form of interviews conducted with Grab drivers and consumers of Grab in the city of Tulungagung. The results of research on the application of services in the field sometimes differ from the provisions of the company in terms of any aspect field workers understand customers better. Services outside the SOP really need to be done as long as they are still at a reasonable level, safe to do, and also make the relationship between the service seller and the customer sustainable. The concept of service is more carried out by a Grab driver with the aim of customer satisfaction and loyalty.